Deorphaning the Macromolecular Targets of the Natural Anticancer Compound Doliculide. (8th September 2016) - Schneider, Gisbert; Reker, Daniel; Chen, Tao; Hauenstein, Kurt; Schneider, Petra; Altmann, Karl‐Heinz
Abstract: The cyclodepsipeptide doliculide is a marine natural product with strong actin‐polymerizing and anticancer activities. Evidence for doliculide acting as a potent and subtype‐selective antagonist of prostanoid E receptor 3 (EP3) is presented. Computational target prediction suggested that this membrane receptor is a likely macromolecular target and enabled immediate in vitro validation. This proof‐of‐concept study demonstrates the in silico deorphanization of phenotypic screening hits as a viable concept for future natural‐product‐inspired chemical biology and drug discovery efforts.